1998
DOI: 10.1046/j.1365-2362.1998.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired release of tissue plasminogen activator from the endothelium in Graves' disease — indicator of endothelial dysfunction and reduced fibrinolytic capacity

Abstract: Hyperthyroid patients may experience vascular endothelial dysfunction and reduced fibrinolytic activity in blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 24 publications
4
30
1
Order By: Relevance
“…Similarly, increased levels of PAI-1 antigen have been reported in patients with both thyroid dysfunctions [20,22]. Results from the few studies evaluating PAI-1 levels in hyperthyroid patients suggest that PAI-1 is elevated in hyperthyroidism [8][9][10]20]. We found lower TAFI and elevated PAI-1 antigen levels in patients with hyperthyroidism.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, increased levels of PAI-1 antigen have been reported in patients with both thyroid dysfunctions [20,22]. Results from the few studies evaluating PAI-1 levels in hyperthyroid patients suggest that PAI-1 is elevated in hyperthyroidism [8][9][10]20]. We found lower TAFI and elevated PAI-1 antigen levels in patients with hyperthyroidism.…”
Section: Discussionsupporting
confidence: 77%
“…Dorr and Volzke [8] showed that decreased serum TSH is an independent risk factor for elevated plasma fibrinogen levels. Li et al [9] reported that serum thyroid hormone concentrations were strongly correlated with plasma PAI-1. Ozcan et al [10] found that elevated PAI-1 antigen levels in hyperthyroid patients decreased after euthyroidism was restored.…”
mentioning
confidence: 99%
“…Except in one study (22), no effect of thyroid status on serum levels of TNF-a has been demonstrated (23)(24)(25)(26). Only a few studies on serum PAI-1 levels have been presented showing an increased level in hyperthyroidism (27) and a decreased level in severe hypothyroidism (28). Taken together with the data on both serum and adipose tissue secretion concentrations in this study, it can be concluded that thyroid status, at least in the case of hyperthyroidism, plays a minor role in the hormonal regulation of leptin and TNF-a.…”
Section: Discussionmentioning
confidence: 93%
“…Some reports have described an increase in serum PAI-1 concentration in hyperthyroidism, whereas others did not detect any differences (7)(8)(9).…”
Section: Introductionmentioning
confidence: 89%